Evolution—the Extended Synthesis 2010
DOI: 10.7551/mitpress/9780262513678.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

High-Dimensional Fitness Landscapes and Speciation

Abstract: The Modern Evolutionary Synthesis of the 1930s and 1940s remains the paradigm of evolutionary biology (Futuyma 1998;Gould 2002;Pigliucci 2007;Ridley 1993). The progress in understanding the process of evolution made during that period had been a direct result of the development of theoretical population genetics by Fisher, Wright, and Haldane, who built a series of mathematical models, approaches, and techniques showing how natural selection, mutation, drift, migration, and other evolutionary factors are expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 90 publications
(135 reference statements)
1
29
0
Order By: Relevance
“…These findings suggest hybridization relaxes genetic constraint, creates new morphological combinations and may thus facilitate phenotypic diversification in response to novel forms of directional and divergent natural selection. Relaxation of the G and P matrices may be particularly important during the early stages of adaptive radiation, when phenotypes are likely to be subjected first to relaxation of previously experienced selection in the ecological release phase (Yoder et al ., ), followed by complex, multidimensional forms of diversifying selection in directions not previously experienced by these populations (Gavrilets, ; Ito & Dieckmann, ). By relaxing constraint, hybridization may first facilitate the expansion to new areas in morphospace in response to ecological release, and second adaptive diversification in response to new diversifying selection in such environments.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest hybridization relaxes genetic constraint, creates new morphological combinations and may thus facilitate phenotypic diversification in response to novel forms of directional and divergent natural selection. Relaxation of the G and P matrices may be particularly important during the early stages of adaptive radiation, when phenotypes are likely to be subjected first to relaxation of previously experienced selection in the ecological release phase (Yoder et al ., ), followed by complex, multidimensional forms of diversifying selection in directions not previously experienced by these populations (Gavrilets, ; Ito & Dieckmann, ). By relaxing constraint, hybridization may first facilitate the expansion to new areas in morphospace in response to ecological release, and second adaptive diversification in response to new diversifying selection in such environments.…”
Section: Discussionmentioning
confidence: 99%
“…Considering how well the restriction enzyme frequency ( Fig 3A) and best sphere packing center density ( Fig 3B) distributions match overall given the biological constraints on the range that restriction enzymes can function in, the sphere packing center density distribution appears to be a measure of fitness for restriction enzymes evolving over a high dimensional adaptive fitness landscape, similar to the high dimensional spaces described by Wright [88][89][90][91].…”
Section: Coding Space As a Fitness Landscapementioning
confidence: 83%
“…This number is typically quite high. Previous work has shown that ridges of similarly elevated fitness tend to be tightly interconnected in such high‐dimensional landscapes (reviewed in Gavrilets, ). Analogous to the genotype networks defined above, these ridges form what are called (nearly) neutral networks (Gavrilets, ; Gavrilets and Gravner, ).…”
Section: Evolution On Fitness Landscapesmentioning
confidence: 99%